Black skin, white coats : Nigerian psychiatrists, decolonization, and the globalization of psychiatry - Heaton, Matthew M. (New African histories series., 2013)
Black Skin, White Coats is a history of psychiatry in Nigeria from the 1950s to the 1980s. Working in the contexts of decolonization and anticolonial nationalism, Nigerian psychiatrists sought to replace racist colonial psychiatric theories about the psychological inferiority of Africans with a universal and egalitarian model focusing on broad psychological similarities across cultural and racial boundaries. Particular emphasis is placed on Dr. T. Adeoye Lambo, the first Indigenous Nigerian to earn a specialty degree in psychiatry in the United Kingdom in 1954. Lambo returned to Nigeria to be.